Autologous cell suspension grafting in segmental vitiligo and piebaldism: a randomized controlled trial comparing full surface and fractional CO2 laser recipient‐site preparations. (1st November 2017) - Lommerts, J.E.; Meesters, A.A.; Komen, L.; Bekkenk, M.W.; de Rie, M.A.; Luiten, R.M.; Wolkerstorfer, A.
Summary: Background: Autologous noncultured cell suspension transplantation is an effective treatment for repigmentation in segmental vitiligo and piebaldism. Full surface laser ablation is frequently used to prepare the recipient site before cell suspension transplantation, even though the optimal laser settings and ablation depth are unknown. Objectives: To assess the efficacy and safety of less invasive recipient‐site preparations. Methods: In a randomized, observer‐blinded, controlled trial we compared different recipient‐site preparations before cell suspension transplantation in segmental vitiligo and piebaldism. In each patient, we randomly allocated three CO2 laser recipient‐site preparations (209 and 144 μm full surface, and fractional) and a control (no treatment) to four depigmentations. After 6 months we assessed repigmentation and side‐effects. Results: We included 10 patients with vitiligo ( n = 3) and piebaldism ( n = 7). Compared with the control site, we found more repigmentation after full surface ablation at 209 μm (median 68·7%, P = 0·01) and 144 μm (median 58·3%, P = 0·007), but no repigmentation after fractional ablation (median 0·0%, P = 0·14). Conclusions: Superficial full surface ablation with a depth of 144 μm is an effective recipient‐site preparation before cell suspension transplantation, while fractional CO2 laser is not.